Pendampingan Pembuatan Digester Biogas Berbasis Portabel Sebagai Alternatif Bahan Bakar dan Penerangan Kandang - Yudha Adi Kusuma; Dyan Hatining Ayu Sudarni (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The manufacture of biogas digesters is one solution to reduce the impact of environmental pollution due to dairy breeding.  Environmental pollution constraints are inevitable for the group of dairy breeders, Nedyo Rahayu. Most breeders have been dumping cow dung on waterways without first putting a shelter process in place. These activities can cause environmental pollution if they take place at any time. Based on existing problems, community development is carried out in the manufacture of biogas digesters as an alternative to preventive measures. Community development is carried out over a period of 3 months, starting from the first week of January 2022 until the final week of March 2022. The results of testing ANOVA's one-way method are known to be methods combined (theory and practice) to be the best methods. The average value of the combined method obtained from group member Nedyo Rahayu is 77.46. With the assistance of manufacturing biogas digesters portable, breeder group Nedyo Rahayu is expected to use the technology for alternative fuels and cage lighting. Portable biogas digester technology provides convenience in terms of maintenance, displacement, and low cost.